Comparative evaluation of three anti-dsDNA antibody detection methods in systemic lupus erythematosus: insights from a large monocentric cohort - Lu, Ruijing; Yu, Rui; Huang, Rong; Xue, Chiyuan; Song, Ning; Zhao, Jiuliang; Zeng, Xiaofeng; Hu, Chaojun (Frontiers in Immunology, 2025)
BackgroundAnti-double-stranded DNA (anti-dsDNA) antibodies at abnormal titer are of considerable diagnostic value for systemic lupus erythematosus (SLE). Current assays detecting anti-dsDNA antibodies show divergent properties, emphasizing the importance of selecting suitable assays. This study aims to investigate the diagnostic performance of indirect immunofluorescence (IIF), digital liquid chip method (DLCM), chemiluminescence immunoassay (CLIA), and their combinations for detecting anti-dsDNA antibodies in SLE.MethodsWe conducted a retrospective, single-center study from 2022 to 2023 which included 3429 samples: 1773 from patients with SLE and 1656 from controls with rheumatoid arthritis (RA) and Sjögren’s syndrome (SS). Sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) for anti-dsDNA detection by IIF, DLCM, and CLIA were calculated. Cohen’s kappa coefficient was used to evaluate inter-method agreement. The correlations between anti-dsDNA concentration and SLEDAI-2k scores/renal involvement were assessed.ResultsAmong individual assays, IIF demonstrated the highest specificity (98.31%) and PPV (96.10%) but lower sensitivity (38.92%) compared to CLIA (41.57%) and DLCM (43.65%) (p < 0.05). Combining two assays significantly improved sensitivity while maintaining specificity>95%. The combination of IIF and DLCM achieved a sensitivity of 52.2% and an AUC of 0.76. Substantial agreement was observed between DLCM and CLIA (κ = 0.78), whereas agreement between IIF and the other assays was moderate (κ = 0.65–0.66). In a longitudinal analysis of 88 SLE patients, CLIA and DLCM detected antibody fluctuations more reliably than IIF. Anti-dsDNA levels by DLCM or CLIA positively correlated with SLEDAI-2K scores (R=0.42 and 0.29, p<0.05). Both IIF and CLIA methods showed significant differences between the SLE patients with and without renal involvement (p < 0.05). The combination of two assays provided higher sensitivity than single assays (p<0.001) in renal involvement subgroups.ConclusionOur findings demonstrate that DLCM performs comparably to CLIA, supporting its clinical potential. Moreover, combining assays significantly enhances diagnostic sensitivity, particularly in subgroups with renal involvement.